CN108821295A - The method that amorphous silica prepares ultrapure quartz sand - Google Patents
The method that amorphous silica prepares ultrapure quartz sand Download PDFInfo
- Publication number
- CN108821295A CN108821295A CN201810820847.2A CN201810820847A CN108821295A CN 108821295 A CN108821295 A CN 108821295A CN 201810820847 A CN201810820847 A CN 201810820847A CN 108821295 A CN108821295 A CN 108821295A
- Authority
- CN
- China
- Prior art keywords
- amorphous silica
- quartz sand
- ultrapure
- kettle
- pressure
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
- VYPSYNLAJGMNEJ-UHFFFAOYSA-N Silicium dioxide Chemical compound O=[Si]=O VYPSYNLAJGMNEJ-UHFFFAOYSA-N 0.000 title claims abstract description 180
- 239000006004 Quartz sand Substances 0.000 title claims abstract description 44
- 238000000034 method Methods 0.000 title claims abstract description 40
- 239000010453 quartz Substances 0.000 claims abstract description 34
- 239000000463 material Substances 0.000 claims abstract description 33
- 238000006243 chemical reaction Methods 0.000 claims abstract description 28
- 239000013078 crystal Substances 0.000 claims abstract description 26
- 229910021642 ultra pure water Inorganic materials 0.000 claims abstract description 14
- 239000012498 ultrapure water Substances 0.000 claims abstract description 14
- 239000007787 solid Substances 0.000 claims abstract description 13
- 238000000926 separation method Methods 0.000 claims abstract description 11
- 239000007788 liquid Substances 0.000 claims abstract description 10
- 238000010438 heat treatment Methods 0.000 claims abstract description 4
- 235000012239 silicon dioxide Nutrition 0.000 claims description 46
- 239000000377 silicon dioxide Substances 0.000 claims description 25
- 229910052681 coesite Inorganic materials 0.000 claims description 15
- 229910052906 cristobalite Inorganic materials 0.000 claims description 15
- 229910052682 stishovite Inorganic materials 0.000 claims description 15
- 229910052905 tridymite Inorganic materials 0.000 claims description 15
- VEXZGXHMUGYJMC-UHFFFAOYSA-N Hydrochloric acid Chemical compound Cl VEXZGXHMUGYJMC-UHFFFAOYSA-N 0.000 claims description 14
- QTBSBXVTEAMEQO-UHFFFAOYSA-N Acetic acid Chemical compound CC(O)=O QTBSBXVTEAMEQO-UHFFFAOYSA-N 0.000 claims description 12
- HEMHJVSKTPXQMS-UHFFFAOYSA-M Sodium hydroxide Chemical compound [OH-].[Na+] HEMHJVSKTPXQMS-UHFFFAOYSA-M 0.000 claims description 12
- QAOWNCQODCNURD-UHFFFAOYSA-N Sulfuric acid Chemical compound OS(O)(=O)=O QAOWNCQODCNURD-UHFFFAOYSA-N 0.000 claims description 10
- KWYUFKZDYYNOTN-UHFFFAOYSA-M Potassium hydroxide Chemical compound [OH-].[K+] KWYUFKZDYYNOTN-UHFFFAOYSA-M 0.000 claims description 9
- QGZKDVFQNNGYKY-UHFFFAOYSA-N Ammonia Chemical compound N QGZKDVFQNNGYKY-UHFFFAOYSA-N 0.000 claims description 8
- NBIIXXVUZAFLBC-UHFFFAOYSA-N Phosphoric acid Chemical compound OP(O)(O)=O NBIIXXVUZAFLBC-UHFFFAOYSA-N 0.000 claims description 8
- CDBYLPFSWZWCQE-UHFFFAOYSA-L Sodium Carbonate Chemical compound [Na+].[Na+].[O-]C([O-])=O CDBYLPFSWZWCQE-UHFFFAOYSA-L 0.000 claims description 8
- BWHMMNNQKKPAPP-UHFFFAOYSA-L potassium carbonate Chemical compound [K+].[K+].[O-]C([O-])=O BWHMMNNQKKPAPP-UHFFFAOYSA-L 0.000 claims description 8
- 239000002253 acid Substances 0.000 claims description 6
- 229910000147 aluminium phosphate Inorganic materials 0.000 claims description 4
- 229910021529 ammonia Inorganic materials 0.000 claims description 4
- 239000000203 mixture Substances 0.000 claims description 4
- 229910000027 potassium carbonate Inorganic materials 0.000 claims description 4
- 229910000029 sodium carbonate Inorganic materials 0.000 claims description 4
- GRYLNZFGIOXLOG-UHFFFAOYSA-N Nitric acid Chemical compound O[N+]([O-])=O GRYLNZFGIOXLOG-UHFFFAOYSA-N 0.000 claims description 3
- 229910017604 nitric acid Inorganic materials 0.000 claims description 3
- 238000004090 dissolution Methods 0.000 claims description 2
- 238000002425 crystallisation Methods 0.000 claims 1
- 230000008025 crystallization Effects 0.000 claims 1
- 239000001257 hydrogen Substances 0.000 claims 1
- 229910052739 hydrogen Inorganic materials 0.000 claims 1
- -1 hydrogen Potassium oxide Chemical class 0.000 claims 1
- 229910001950 potassium oxide Inorganic materials 0.000 claims 1
- 239000004575 stone Substances 0.000 claims 1
- 239000004576 sand Substances 0.000 abstract description 16
- 239000011521 glass Substances 0.000 abstract description 13
- 239000012535 impurity Substances 0.000 description 10
- 238000004519 manufacturing process Methods 0.000 description 7
- 239000002245 particle Substances 0.000 description 5
- XLYOFNOQVPJJNP-UHFFFAOYSA-N water Substances O XLYOFNOQVPJJNP-UHFFFAOYSA-N 0.000 description 5
- 238000005516 engineering process Methods 0.000 description 4
- 230000003287 optical effect Effects 0.000 description 4
- 239000002994 raw material Substances 0.000 description 4
- 230000008030 elimination Effects 0.000 description 3
- 238000003379 elimination reaction Methods 0.000 description 3
- 238000002360 preparation method Methods 0.000 description 3
- 239000000126 substance Substances 0.000 description 3
- XEEYBQQBJWHFJM-UHFFFAOYSA-N Iron Chemical compound [Fe] XEEYBQQBJWHFJM-UHFFFAOYSA-N 0.000 description 2
- 238000004458 analytical method Methods 0.000 description 2
- 239000000084 colloidal system Substances 0.000 description 2
- 229910002026 crystalline silica Inorganic materials 0.000 description 2
- 238000011161 development Methods 0.000 description 2
- 238000001035 drying Methods 0.000 description 2
- 230000010354 integration Effects 0.000 description 2
- 238000005554 pickling Methods 0.000 description 2
- 238000005498 polishing Methods 0.000 description 2
- 238000012827 research and development Methods 0.000 description 2
- 238000005070 sampling Methods 0.000 description 2
- 239000000725 suspension Substances 0.000 description 2
- 210000003462 vein Anatomy 0.000 description 2
- VHUUQVKOLVNVRT-UHFFFAOYSA-N Ammonium hydroxide Chemical compound [NH4+].[OH-] VHUUQVKOLVNVRT-UHFFFAOYSA-N 0.000 description 1
- 241000790917 Dioxys <bee> Species 0.000 description 1
- DGAQECJNVWCQMB-PUAWFVPOSA-M Ilexoside XXIX Chemical compound C[C@@H]1CC[C@@]2(CC[C@@]3(C(=CC[C@H]4[C@]3(CC[C@@H]5[C@@]4(CC[C@@H](C5(C)C)OS(=O)(=O)[O-])C)C)[C@@H]2[C@]1(C)O)C)C(=O)O[C@H]6[C@@H]([C@H]([C@@H]([C@H](O6)CO)O)O)O.[Na+] DGAQECJNVWCQMB-PUAWFVPOSA-M 0.000 description 1
- 102000004160 Phosphoric Monoester Hydrolases Human genes 0.000 description 1
- 108090000608 Phosphoric Monoester Hydrolases Proteins 0.000 description 1
- 229910003978 SiClx Inorganic materials 0.000 description 1
- XUIMIQQOPSSXEZ-UHFFFAOYSA-N Silicon Chemical compound [Si] XUIMIQQOPSSXEZ-UHFFFAOYSA-N 0.000 description 1
- 238000010306 acid treatment Methods 0.000 description 1
- 239000004411 aluminium Substances 0.000 description 1
- XAGFODPZIPBFFR-UHFFFAOYSA-N aluminium Chemical compound [Al] XAGFODPZIPBFFR-UHFFFAOYSA-N 0.000 description 1
- 229910052782 aluminium Inorganic materials 0.000 description 1
- 239000000908 ammonium hydroxide Substances 0.000 description 1
- 230000009286 beneficial effect Effects 0.000 description 1
- 238000001816 cooling Methods 0.000 description 1
- 238000005090 crystal field Methods 0.000 description 1
- 238000001514 detection method Methods 0.000 description 1
- 235000021050 feed intake Nutrition 0.000 description 1
- 238000000227 grinding Methods 0.000 description 1
- 238000001027 hydrothermal synthesis Methods 0.000 description 1
- XLYOFNOQVPJJNP-UHFFFAOYSA-M hydroxide Chemical compound [OH-] XLYOFNOQVPJJNP-UHFFFAOYSA-M 0.000 description 1
- 229910052500 inorganic mineral Inorganic materials 0.000 description 1
- 229910052742 iron Inorganic materials 0.000 description 1
- 238000007885 magnetic separation Methods 0.000 description 1
- 239000011707 mineral Substances 0.000 description 1
- 238000002156 mixing Methods 0.000 description 1
- 238000012986 modification Methods 0.000 description 1
- 230000004048 modification Effects 0.000 description 1
- 239000002159 nanocrystal Substances 0.000 description 1
- 229910021420 polycrystalline silicon Inorganic materials 0.000 description 1
- 229920005591 polysilicon Polymers 0.000 description 1
- 238000012805 post-processing Methods 0.000 description 1
- FGIUAXJPYTZDNR-UHFFFAOYSA-N potassium nitrate Chemical compound [K+].[O-][N+]([O-])=O FGIUAXJPYTZDNR-UHFFFAOYSA-N 0.000 description 1
- 238000012545 processing Methods 0.000 description 1
- 238000000746 purification Methods 0.000 description 1
- 238000012797 qualification Methods 0.000 description 1
- 238000010791 quenching Methods 0.000 description 1
- 230000000171 quenching effect Effects 0.000 description 1
- 238000011160 research Methods 0.000 description 1
- 238000012216 screening Methods 0.000 description 1
- 238000004062 sedimentation Methods 0.000 description 1
- 239000004065 semiconductor Substances 0.000 description 1
- 229910052710 silicon Inorganic materials 0.000 description 1
- 239000010703 silicon Substances 0.000 description 1
- 239000011734 sodium Substances 0.000 description 1
- 229910052708 sodium Inorganic materials 0.000 description 1
- 238000003756 stirring Methods 0.000 description 1
- 238000012360 testing method Methods 0.000 description 1
- 238000005406 washing Methods 0.000 description 1
- 239000002699 waste material Substances 0.000 description 1
- 238000001238 wet grinding Methods 0.000 description 1
Classifications
-
- C—CHEMISTRY; METALLURGY
- C01—INORGANIC CHEMISTRY
- C01B—NON-METALLIC ELEMENTS; COMPOUNDS THEREOF; METALLOIDS OR COMPOUNDS THEREOF NOT COVERED BY SUBCLASS C01C
- C01B33/00—Silicon; Compounds thereof
- C01B33/113—Silicon oxides; Hydrates thereof
- C01B33/12—Silica; Hydrates thereof, e.g. lepidoic silicic acid
-
- C—CHEMISTRY; METALLURGY
- C01—INORGANIC CHEMISTRY
- C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
- C01P2006/00—Physical properties of inorganic compounds
- C01P2006/80—Compositional purity
Landscapes
- Chemical & Material Sciences (AREA)
- Organic Chemistry (AREA)
- Inorganic Chemistry (AREA)
- Silicon Compounds (AREA)
Abstract
The invention proposes a kind of methods that amorphous silica prepares ultrapure quartz sand, including:Amorphous silica, mineralizer and ultrapure water are added in a kettle;Heating dissolves amorphous silica;Quartzy nucleus is added in the reaction kettle, gradually reduces the temperature and pressure in reaction kettle later, quartzy nuclei growth is quartz crystal;When quartz crystal granularity is greater than 48 μm or more, the pressure and temperature of reaction kettle is reduced, material is drawn off;It is separated by solid-liquid separation the material;Dry solids, as ultrapure quartz sand.Product quality produced by the present invention is high;Glass sand is up to 6N grades.
Description
Technical field
The present invention relates to the preparation field of ultrapure quartz sand, particularly relate to be related to a kind of amorphous silica prepare it is ultrapure
The method of quartz sand.
Background technique
Quartz sand is that nature is most common, one of most widely used nonmetallic ore raw material.Quartz ware is with its uniqueness
High high-temp stability (such as 1200 DEG C of direct water-coolings, quartz glass do not burst), excellent optical property and superpower machinery and
Chemical property is widely used in the high-technology fields such as electronics industry, semiconductor, solar energy, laser and aerospace.With
High-tech area is continuously increased high-quality quartz application, increasing to the demand of glass sand, produces to quartz sand
The quality requirements of product are higher and higher;One notable feature of glass sand product, be SiO2 >=99.99% in product~
99.9999%, and iron content, the content of aluminium are limited in very low range.Silica crucible for silicon single crystal rod drawing
Quartz sand, or even require all impurity contents be less than 6ppm.This quartz sand China can't produce, all from foreign countries into
Mouthful, price per ton is up to 80,000 yuan of RMB.
Countries in the world always to glass sand production technology and equipment carry out unremitting research and development, it is high to meet this country
New technical field develops the demand to glass sand.China also there are many R&D institution and manufacturing company research and develop it is high-purity
Quartz sand product, and have some patent disclosures.
A kind of method using quartz tail sand preparation ultrafine crystalline silica of 103101919 A of patent CN, by right
The wet grinding and pickling of quartz tail sand obtain ultra-fine crystalline silica;After complicated procedures of forming operation, average particle size ruler is obtained
The very little silica for being 200 ± 30nm;But final products dioxide-containing silica can only be improved than raw material an order of magnitude (such as from
SiO2 >=99% is increased to SiO2 >=99.9%).
The method that patent CN 101948235A prepares glass sand, by quartz mine artificial separation, roughing, forge
The processes such as burning, water quenching, crushing, selected pickling, separation, drying, magnetic separation, screening remove the impurity in quartz mine, make
SiO2 >=99.99% of portioned product is obtained, SiO2 >=99.95% of portioned product separately has portioned product SiO2 >=99.90%.
This method complex process, there are waste acid treatment problems, and dioxide-containing silica is still reached to less than monocrystalline silica crucible institute in product
The quality requirement needed.
The method that patent CN1225513C uses vein quartz to prepare superfine high-purity quartz material, using domestic high-quality vein quartz
(SiO2 >=99%) is raw material, through coarse crushing, the impurity elimination of electrostatic separation method, ultra-fine grinding, high-gradient magnetic method impurity elimination, microwave treatment, network
The processes such as legal impurity elimination and post-processing make SiO2 content up to 99.99%~99.999%, impurity content < 100ppm.This is specially
Sharp complex process, manufacturing cost is high, and impurity content can only achieve less than 100ppm in product, is wanted with polysilicon crucible with quartz sand
Impurity content is asked to compare less than 6ppm, there are larger gaps.
The method that 102618926 B of patent CN prepares ball shaped nano single crystal quartz particle, using nanoscale silica
Colloid is raw material, and the processes such as hydro-thermal reaction, centrifugal sedimentation, washing, drying are carried out under through mixing, stirring condition, obtain list
Dispersing ball nano crystal quartz particles;The ball shaped nano quartz particles can be used for super large-scale integration encapsulating material and
Semicon industry, precision valve, hard disc, surface polishing treatment of magnetic head etc..Since silicon dioxide colloid is unformed dioxy
SiClx, amorphous silica under " reaction temperature is 150~230 DEG C, pressure is 5~20 atmospheric pressure " process conditions, be for
Ball shaped nano single crystal quartz particle is prepared, for use in " super large-scale integration encapsulating material and semicon industry, precision
Valve, hard disc, surface polishing treatment of magnetic head etc. ".The main points of the technology be in order to which the quartz of preparation is in nanoscale, and
Non- quartz sand.
The method of patent CN100335683C method for preparing large-size artificial optical quartz crystal by hydrothermal, using the hydro-thermal temperature difference
Method grows crystal in autoclave.The patent procedure pressure high (pressure P=145~150MPa), the temperature difference control the stringent (temperature difference
T=30 DEG C of Δ~50 DEG C), seed orientation directly affects crystalline quality (seed orientation is:Using Y-axis as length direction, X-axis is width
Direction is spent, Z axis is the direction of growth);Growth rate is slow, but can grow large scale quartz crystal (having a size of Z=240-
250mm, X=140-150mm, Y=290mm, weight=20-25Kg).Crystal is colorless and transparent, flawless, bubble, twin crystal, growth
Mound is smooth;Product qualification rate is high, and therefore, high production cost, the scope of application is " large scale optical delay piece and other needs
Large-sized optical crystal field ";It is characterized in that prepare large-sized crystalline.Obviously, such quartz crystal
It can not be used to manufacture high-purity silica pot.
The quartz sand purification by mineral and deep processing development in China are started late, and domestic high grade quartz sand resource is relatively
Few, the prior art can't produce the glass sand product that impurity content is less than 6ppm.How a kind of low cost production is developed
The technology of glass sand product, to meet the needs of China's high-tech sector is to glass sand, to promotion China its people warp
Ji development has great importance.
Summary of the invention
Invention proposes a kind of method that amorphous silica prepares ultrapure quartz sand, solves and prepares in the prior art
The high problem of quartz sand impurity content.
The technical proposal of the invention is realized in this way:
A kind of method that amorphous silica prepares ultrapure quartz sand, including:
Amorphous silica, mineralizer and ultrapure water are added in a kettle;Heating dissolves amorphous silica;
Quartzy nucleus is added in the reaction kettle, gradually reduces the temperature and pressure in reaction kettle, quartzy nucleus later
Long greatly quartz crystal;When quartz crystal granularity is greater than 48 μm or more, the pressure and temperature of reaction kettle is reduced, material is drawn off;
It is separated by solid-liquid separation the material;Dry solids, as ultrapure quartz sand.
The amorphous silica is dissolved in the technique in the mineralizer and ultrapure water as a preferred technical solution,
Condition is:250-330 DEG C of temperature, pressure 25-90MPa.
Before material is drawn off as a preferred technical solution, set the pressure of reaction kettle as normal pressure~20MPa, temperature be normal
Temperature~200 DEG C.
When the quartz crystal granularity is greater than 48 μm or/and less than 500 μm as a preferred technical solution, reaction is reduced
The pressure and temperature of kettle, draws off material.
The mineralizer is fluosilicic acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, hydroxide as a preferred technical solution,
One of sodium, potassium hydroxide, sodium carbonate, potassium carbonate, ammonia.It is furthermore preferred that the mineralizer is fluosilicic acid, hydrochloric acid, sulfuric acid, nitre
Several mixtures in the substances such as acid, phosphoric acid, acetic acid;Or the substances such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, ammonia
In several mixtures.
The amorphous silica is that content is greater than 99.99% (SiO2 >=99.99%) as a preferred technical solution,
Armorphous material.
The quartzy nucleus is SiO as a preferred technical solution,2>=99.99%, crystal form object of the granularity less than 25 μm
Material.The quartz nucleus is directly crushed gained by glass sand.
The quartzy nucleus is mixed with ultrapure water as a preferred technical solution, is formed suspended state, is pressed by pressure
In the reaction kettle.
The material after the separation of solid and liquid is cleaned with ultrapure dilute hydrochloric acid or/and ultrapure water as a preferred technical solution,.
The reaction kettle is composed in series by 2~6 as a preferred technical solution,:1st reaction kettle is as silica
Dissolution kettle;Subsequent several reaction kettles sequentially form temperature and pressure as quartz crystals kettle, and between each quartz crystals kettle
It is differential;Material successively flows to subsequent several high pressure resistant kettles from first high pressure resistant kettle.
The content of the ultrapure quartz sand is SiO as a preferred technical solution,2>=99.999%;Even super pure silica
The content of sand is SiO2>=99.9999%.
Pressure in the present invention in reaction kettle be added by water it is thermogenetic by mineralizer add it is thermogenetic or by
What the high pressure gas being connected with reaction kettle was added.
Beneficial effect
1, product quality is high;Glass sand is up to 6N grades.
2, with low investment, simple process, low production cost.
3, new market purposes has been opened up for amorphous silica.
4, ultrapure quartz sand is manufactured for large-scale low-cost provide technical guarantee.
Specific embodiment
The technical scheme in the embodiments of the invention will be clearly and completely described below, it is clear that described implementation
Example is only a part of the embodiment of the present invention, instead of all the embodiments.Based on the embodiments of the present invention, this field is common
Technical staff's every other embodiment obtained without making creative work belongs to the model that the present invention protects
It encloses.
Embodiment 1
A kind of method that amorphous silica prepares ultrapure quartz sand, includes the following steps:
Step S1:50kg amorphous silica, mineralizer and 2500kg ultrapure water are added in the first high pressure resistant kettle, adds
Heat makes 250 DEG C of temperature in the first high pressure resistant kettle, and keeping pressure in kettle is 30MPa.Mineralizer selection is in the present embodiment
95% sodium hydroxide 55kg and 25% ammonium hydroxide 20kg.
Step S2:The dissolved material of step S1 enters in the second high pressure resistant kettle, and SiO is added simultaneously2>=99.99%,
Quartzy nucleus of the granularity less than 25 μm, quartzy nucleus are sufficiently mixed before reaction kettle is added with ultrapure water, and suspended state is formed, and are led to
Excess pressure is pressed into reaction kettle.Temperature in the kettle and pressure are slowly reduced later, and keeping temperature is 220 DEG C, holding pressure is
25MPa.Quartzy nucleus gradually grows greatly quartz sand.
Step S3:After 4 hours, quartz crystal granularity has been greater than 48 μm in the high pressure resistant kettle of sample detection second;It is resistance to second
Temperature in autoclave be gradually down to 200 DEG C, pressure be down to 20MPa.Draw off the material in the second high pressure resistant kettle.Keep second resistance to
Temperature and pressure in autoclave can be to feed intake again the energy saving and time in suitable numerical value.
Step S4:After separation of solid and liquid, solids is cleaned with high purity hydrochloric acid thin liquid (10% content), then cleaned 3 times with pure water.
Dry solids, as ultrapure quartz sand.
Embodiment 2
A kind of method that amorphous silica prepares ultrapure quartz sand, includes the following steps:
Step S1:100kg amorphous silica, mineralizer and 3000kg ultrapure water are added in the first high pressure resistant kettle,
Heating makes the first 330 DEG C of high pressure resistant temperature in the kettle, and keeping pressure in kettle is 35MPa.What the mineralizer in the present embodiment was selected
It is 98% sulfuric acid 95kg and 35% fluosilicic acid 100kg.
Step S2:The dissolved material of step S1 enters in the second high pressure resistant kettle, and the suspension of quartzy nucleus is added simultaneously
Liquid, keep the second high pressure resistant kettle temperature be 315 DEG C, pressure 33MPa.Material stop 40 minutes.
Step S3:The material of step S2 enters in the high pressure resistant kettle of third, keep the high pressure resistant kettle of third temperature be 280 DEG C,
Pressure is 31MPa.Material stop 40 minutes.
Step S4:The material of step S3 enter the 4th high pressure resistant kettle in, keep the 4th high pressure resistant kettle temperature be 250 DEG C,
Pressure is 29MPa.Material stop 40 minutes.
Step S5:The material of step S4 enter the 5th high pressure resistant kettle in, keep the 5th high pressure resistant kettle temperature be 250 DEG C,
Pressure is 25MPa.
Step S6:From the 5th high pressure resistant kettle sampling analysis quartz crystal granularity, when above-mentioned quartz crystal granularity is greater than 48 μm
When above, the temperature in the 5th high pressure resistant kettle is gradually reduced to 200 DEG C, pressure reduction to 20MPa.Draw off the 5th high pressure resistant kettle
Interior material.
Step S7:After separation of solid and liquid, solids is cleaned with pure water;Dry solids, as ultrapure quartz sand.
Embodiment 3
A kind of method that amorphous silica prepares ultrapure quartz sand, includes the following steps:
Step S1:80kg amorphous silica, mineralizer and 2500kg ultrapure water are added in high pressure resistant kettle, heats,
Make 280 DEG C of temperature in the first high pressure resistant kettle, keeping pressure in kettle is 90MPa;What mineralizer in the present embodiment was selected is
32% hydrochloric acid 110kg and 50% phosphatase 79 0kg.
Step S2:Quartzy nucleus is added into high pressure resistant kettle, quartzy nucleus is SiO2>=99.99%, granularity is less than 25 μm
Crystal form material, directly crushed by glass sand gained;It is sufficiently mixed before reaction kettle is added with ultrapure water, forms suspension
State is pressed into reaction kettle by pressure.Temperature in the kettle and pressure are slowly reduced later, and quartzy nucleus gradually grows greatly quartz sand.
Step S3:When the above-mentioned quartz sand size of sampling analysis is greater than 200 μm or more, the pressure in high pressure resistant kettle is gradually dropped
It is reduced to room temperature down to normal pressure, temperature, draws off the material in the second high pressure resistant kettle.
Step S4:After separation of solid and liquid, solids is cleaned with pure water;Dry solids, as ultrapure quartz sand.
Embodiment product testing index value such as table 1.
As it can be seen from table 1 the purity of glass sand has reached 99.9999% (6N grades).
The foregoing is merely illustrative of the preferred embodiments of the present invention, is not intended to limit the invention, all in essence of the invention
Within mind and principle, any modification, equivalent replacement, improvement and so on be should all be included in the protection scope of the present invention.
Claims (10)
1. a kind of method that amorphous silica prepares ultrapure quartz sand, which is characterized in that including:
Amorphous silica, mineralizer and ultrapure water are added in a kettle;Heating dissolves amorphous silica;
Quartzy nucleus is added in the reaction kettle, gradually reduces the temperature and pressure in reaction kettle, quartzy nuclei growth later
For quartz crystal;When quartz crystal granularity is greater than 48 μm, the pressure and temperature of reaction kettle is reduced, material is drawn off;
It is separated by solid-liquid separation the material;Dry solids, as ultrapure quartz sand.
2. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
Stating the process conditions that amorphous silica is dissolved in the mineralizer and ultrapure water is:250-330 DEG C of temperature, pressure 25-
90MPa。
3. the method that a kind of amorphous silica according to claim 1 or 2 prepares ultrapure quartz sand, feature exist
In, before material is drawn off, set the pressure of reaction kettle as normal pressure~20MPa, temperature be room temperature~200 DEG C.
4. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
When stating quartz crystal granularity greater than 48 μm or/and less than 500 μm, the pressure and temperature of reaction kettle is reduced, material is drawn off.
5. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
Stating mineralizer is fluosilicic acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, ammonia
One of;Or
The mineralizer is fluosilicic acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, several mixtures in acetic acid;Or sodium hydroxide, hydrogen
Potassium oxide, sodium carbonate, potassium carbonate, several mixtures in ammonia.
6. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
State the armorphous material that amorphous silica is SiO2 >=99.99%;
The quartz nucleus is SiO2>=99.99%, crystal form material of the granularity less than 25 μm;The quartz nucleus is by high purity quartz
Sand directly crushes gained.
7. the method that a kind of amorphous silica according to claim 6 prepares ultrapure quartz sand, which is characterized in that institute
It states quartzy nucleus to mix with ultrapure water, forms suspended state, be pressed into the reaction kettle by pressure.
8. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
The material after being separated by solid-liquid separation is stated to be cleaned with ultrapure dilute hydrochloric acid or/and ultrapure water.
9. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that institute
Reaction kettle is stated to be composed in series by 2~6:1st reaction kettle is as silica dissolution kettle;Subsequent several reaction kettles are as stone
English crystallization kettle, and the differential of temperature and pressure is sequentially formed between each quartz crystals kettle;Material from first high pressure resistant kettle according to
It is secondary to flow to subsequent several high pressure resistant kettles.
10. the method that a kind of amorphous silica according to claim 1 prepares ultrapure quartz sand, which is characterized in that
The content of the ultrapure quartz sand is SiO2>=99.99%;Even the content of ultrapure quartz sand is SiO2>=99.9999%.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201810820847.2A CN108821295A (en) | 2018-07-24 | 2018-07-24 | The method that amorphous silica prepares ultrapure quartz sand |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201810820847.2A CN108821295A (en) | 2018-07-24 | 2018-07-24 | The method that amorphous silica prepares ultrapure quartz sand |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| CN108821295A true CN108821295A (en) | 2018-11-16 |
Family
ID=64140338
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201810820847.2A Pending CN108821295A (en) | 2018-07-24 | 2018-07-24 | The method that amorphous silica prepares ultrapure quartz sand |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN108821295A (en) |
Cited By (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN111498854A (en) * | 2019-01-31 | 2020-08-07 | 新疆硅基新材料创新中心有限公司 | A kind of method for preparing quartz sand by supercritical water oxidation |
| CN111646480A (en) * | 2020-06-12 | 2020-09-11 | 河南大学 | A kind of crystalline nano silicon dioxide and preparation method thereof |
| CN116444135A (en) * | 2023-03-15 | 2023-07-18 | 新沂市中大石英科技有限公司 | Preparation method of high-purity quartz sand with purity reaching raw material grade of quartz glass crucible |
| CN116873943A (en) * | 2023-08-07 | 2023-10-13 | 安徽壹石通材料科技股份有限公司 | A kind of preparation method of high-purity cristobalite |
| CN118183758A (en) * | 2024-04-22 | 2024-06-14 | 中触媒新材料股份有限公司 | A method for synthesizing high-purity silicon dioxide crystals by sequential online replenishment |
| CN119976862A (en) * | 2025-02-14 | 2025-05-13 | 江苏弘扬石英制品有限公司 | Preparation technology of ultra-high purity amorphous silicon dioxide synthetic quartz sand |
Citations (3)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| KR20040089920A (en) * | 2003-04-15 | 2004-10-22 | (주) 보람케메탈 | The method for preparing the nano silica crystalline powder using the fumed silica |
| US20110143063A1 (en) * | 2009-04-28 | 2011-06-16 | Shin-Etsu Quartz Products Co., Ltd. | Silica container and method for producing the same |
| CN102553291A (en) * | 2012-02-29 | 2012-07-11 | 中粮生物化学(安徽)股份有限公司 | Cooling crystallization method |
-
2018
- 2018-07-24 CN CN201810820847.2A patent/CN108821295A/en active Pending
Patent Citations (3)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| KR20040089920A (en) * | 2003-04-15 | 2004-10-22 | (주) 보람케메탈 | The method for preparing the nano silica crystalline powder using the fumed silica |
| US20110143063A1 (en) * | 2009-04-28 | 2011-06-16 | Shin-Etsu Quartz Products Co., Ltd. | Silica container and method for producing the same |
| CN102553291A (en) * | 2012-02-29 | 2012-07-11 | 中粮生物化学(安徽)股份有限公司 | Cooling crystallization method |
Non-Patent Citations (1)
| Title |
|---|
| 化学工业出版社, 化学工业出版社 * |
Cited By (10)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN111498854A (en) * | 2019-01-31 | 2020-08-07 | 新疆硅基新材料创新中心有限公司 | A kind of method for preparing quartz sand by supercritical water oxidation |
| CN111646480A (en) * | 2020-06-12 | 2020-09-11 | 河南大学 | A kind of crystalline nano silicon dioxide and preparation method thereof |
| CN111646480B (en) * | 2020-06-12 | 2021-12-28 | 河南大学 | Crystalline nano silicon dioxide and preparation method thereof |
| CN116444135A (en) * | 2023-03-15 | 2023-07-18 | 新沂市中大石英科技有限公司 | Preparation method of high-purity quartz sand with purity reaching raw material grade of quartz glass crucible |
| CN116873943A (en) * | 2023-08-07 | 2023-10-13 | 安徽壹石通材料科技股份有限公司 | A kind of preparation method of high-purity cristobalite |
| CN116873943B (en) * | 2023-08-07 | 2024-02-23 | 安徽壹石通材料科技股份有限公司 | Preparation method of high-purity cristobalite |
| WO2025030863A1 (en) * | 2023-08-07 | 2025-02-13 | 安徽壹石通材料科技股份有限公司 | Method for preparing high-purity cristobalite |
| CN118183758A (en) * | 2024-04-22 | 2024-06-14 | 中触媒新材料股份有限公司 | A method for synthesizing high-purity silicon dioxide crystals by sequential online replenishment |
| CN119976862A (en) * | 2025-02-14 | 2025-05-13 | 江苏弘扬石英制品有限公司 | Preparation technology of ultra-high purity amorphous silicon dioxide synthetic quartz sand |
| CN119976862B (en) * | 2025-02-14 | 2025-10-03 | 江苏弘扬石英制品有限公司 | Preparation process of ultra-high purity amorphous silicon dioxide synthetic quartz sand |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN108821294A (en) | The method for preparing ultrapure quartz sand as raw material using common quartz sand | |
| CN108675310A (en) | The method for preparing ultrapure quartz sand as raw material using fluosilicic acid | |
| CN107555426B (en) | Low-energy-consumption large-batch preparation process of high-purity microcrystalline graphite and high-purity microcrystalline graphite prepared by same | |
| CN101948235A (en) | Method for preparing high-purity quartz sand | |
| CN103114333B (en) | The preparation method of monocrystalline spherical silica particle | |
| CN102674378A (en) | Method for preparing silicon dioxide micropowder from natural vein quartz | |
| CN102180584A (en) | Method for removing gas-liquid inclusion and impurity during high-purity quartz sand production | |
| CN112551534B (en) | A kind of preparation method of ultrapure spherical quartz sand | |
| CN108752003B (en) | Preparation method of silicon carbide micro powder for silicon carbide fine ceramic | |
| CN104047048A (en) | Novel ingot casting crucible and manufacturing method thereof | |
| JP2617822B2 (en) | Method for producing non-sintered cristobalite particles | |
| CN112357955B (en) | Method for preparing titanium dioxide powder with different morphologies by solid phase method | |
| CN106082239A (en) | A kind of high-purity low-iron quartz sand purifying preparation method | |
| CN113307275A (en) | Preparation method of high-purity crystalline silica particles | |
| CN103112862A (en) | Method for producing fused obtuse quartz sand from quartz crucibles | |
| CN109111101A (en) | A kind of purification by mineral method of glass sand | |
| CN111233308A (en) | Opaque quartz glass ingot and preparation method thereof | |
| CN102618926B (en) | Method for preparing spherical nanomonocrystalline particle | |
| RU2394764C1 (en) | Method of producing silicon dioxide | |
| CN111762789A (en) | Method for purifying quartz by directional solidification | |
| CN108793176A (en) | The method for preparing ultrapure quartz sand as raw material using ocratation | |
| CN111039322A (en) | Preparation method of high-activity zirconia | |
| CN109809482B (en) | Preparation method of monodisperse multi-morphology zirconia powder | |
| CN119349865A (en) | A high-purity quartz lump and its preparation method and application | |
| CN102583515A (en) | A method for preparing CaTiO3 composite material by slowly cooling titanium-containing blast furnace slag |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| RJ01 | Rejection of invention patent application after publication | ||
| RJ01 | Rejection of invention patent application after publication |
Application publication date: 20181116 |